Pelatihan Perhitungan Harga Jual untuk Pelaku Usaha Mikro Kecil dan Menengah “My Cheese” - Jurica Lucyanda; Monica Weni Pratiwi; Holila Hatta; Raka Muhammad Hasbie; Sarah Novita Asa; Khairun Najwa Mubarok (LPkM Universitas Bakrie, 2026)
Higher education is one of the institutions responsible for supporting Micro, Small, and Medium Enterprises (MSMEs) in their business. This responsibility is to foster MSMEs, enabling them to develop and contribute to economic growth. The purpose of this community service (PkM) is to increase the knowledge and understanding of the importance of calculating the cost of production and selling price for MSME actors. MSMEs are a rapidly growing business and support economic growth in Indonesia. Currently, there are problems faced by MSME actors in computing the cost of production and the selling price. This problem is caused by the limited knowledge and understanding of MSME actors in determining the cost of production and the selling price. Based on these problems, it is necessary to have training activities on the calculation of the cost of production and the selling prices for MSME actors. The partners of this activity are MSMEs that produce cheese sticks under the